Analisis Kesulitan Membaca Lancar Pada Peserta Didik Kelas IV - Siti Nurhikmah Aprianti (Jurnal DIDIKA: Wahana Ilmiah Pendidikan Dasar, 2023)
This study aims to analyze students' difficulties in reading fluently in class IV and to find out what solutions are appropriate in overcoming students' difficulties in reading fluently. The type of research used is qualitative with descriptive method. Data collection used interview, observation, and documentation methods. The difficulty in reading fluently is due to the attention that is too focused on the decoding process, students also read using tools such as fingers that make it difficult for students to concentrate. Learners who cannot read will have difficulty in following the learning process and difficulty in capturing and understanding information. This problem is one of the urgent problems both in the school environment and in the surrounding environment. The utilization of media in the classroom to support learning is only based on reading books, which causes students to be less interested in reading. So the solution provided is to provide alternative learning media that is in accordance with the problems of students, because the problem of students having difficulty reading fluently, the media used is the 'Letter Card' media which is a tool used to assist students in developing basic reading skills. Key words: learners, reading difficulties, reading fluently.